The power of strangers in Flores and Timor - Barnes, R (Anthropos Institute, 2008)
Pitt-Rivers notes that the stranger is dangerous and sacred because he belongs to an extraordinary world and must be "socialised, that is to say secularised, a process which necessarily involves inversion." A striking feature of the traditional histories of several local state structures in eastern Indonesia is how often they maintained ruling authority is in the hands of persons whose ancestors came as strangers and successfully became absorbed into the local communities, often by means of just this sort of inversion. Another recurring pattem is that of the outsider taking active leadership, while indigenous authority remains relatively immobile. This essays looks at several examples an Timor and Flores of attempts to cope with the disjunction of status and power such as Dumont attributed to India and with the constructive dilemma of how to combine legitimacy of authority with the prestige of the stranger.